Pemberdayaan Perempuan Dalam Kewirausahaan Sosial(Studi Kasus Waroeng Hijau, Ancol) - Yudithadewi, Dien; Parikesit, Bonifasius; Sudarmanti, Rini (UI Scholars Hub, 2020)
This research focuses on social entrepreneurship called Waroeng Hijau, which was initiated by one of the Regional Owned Enterprises since 2008. Waroeng Hijau is a women's empowerment program to address social issues in the Pademangan Sub-district, North Jakarta. This study uses a persuasive case approach (Siggelkow, 2007) to see the institutional structure or business model of social entrepreneurship that supports women's empowerment. The data collection process is carried out through literature review and interviews with relevant stakeholders. The results of the study stated that the innovative management model and funding, equality, and mutual cooperation became elements of empowerment that support social entrepreneurship performance.